Agricultural crop consumption induces precocious maturity in deer by improving physical and reproductive performance. Issue 4 (23rd April 2021) - Hata, Ayaka; Nakashita, Rumiko; Anezaki, Tomoko; Minami, Masato; Fukue, Yuko; Higuchi, Naoko; Uno, Hikaru; Nakajima, Yasuhiro; Saeki, Midori; Kozakai, Chinatsu; Takada, Mayura B.
Abstract: Anthropogenic foods such as agricultural crops have potential to give large impacts on wildlife populations. However, few studies have addressed the impact of anthropogenic food consumption on the individual performance and then population of long‐lived mammals such as large herbivores. In this study, we investigated the effect of agricultural crop consumption on the physical characteristics and reproductive performances of sika deer ( Cervus nippon ) in central Japan. To investigate the relative dietary contribution of agricultural crops for each individual, we performed nitrogen stable isotope analysis of bone collagen. Our results suggest that nitrogen stable isotope ratios (δ 15 N) could be used as an index of the relative dietary contribution of agricultural crops. The δ 15 N value of agricultural crops was much higher than that of wild plants and that of bone collagen varied widely among individuals. Deer ≤4 yr old that were more likely to consume agricultural crops tended to be larger and have a higher reproductive rate. In contrast, body size and reproductive rate did not vary according to the relative dietary contribution of agricultural crops in individuals ≥5 yr old. These results indicate that consumption of anthropogenic foods can induce precocious maturity in younger individuals by improving their physical characteristics and reproductive performance. Agricultural crop consumption is therefore likely to be an important factor in the population dynamics of large herbivores living in agricultural landscapes.